2010
DOI: 10.1002/cbic.201000509
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Antifreeze Glycoproteins and Mimics

Abstract: Antifreeze glycoproteins are an important class of biological antifreezes that have potential applications in many areas of medicine, agriculture and industry in which ice crystal growth is damaging. While the synthesis of antifreeze glycoproteins as pure glycoforms has recently been achieved by using ligation and polymerisation strategies, the routine production of large quantities of pure glycoforms remains challenging. A range of C-linked analogues that are readily produced by solid-phase synthesis have del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 99 publications
(123 reference statements)
0
28
0
Order By: Relevance
“…Recently, Steven et al claimed the dendrimer-like AFPs showed higher TH values [213], and Phippen et al demonstrated 12 AFP-fused protein cage nanoparticles that increased the TH value to more than 50-fold that of monomeric AFP [214]. A few groups have attempted to synthesize AFP or AFGP derivatives to elucidate the underlying mechanism of action and to develop practical applications [215,216,217,218,219,220,221]. Another interesting approach is the development of cell-internalizable or -penetrating AFPs.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Recently, Steven et al claimed the dendrimer-like AFPs showed higher TH values [213], and Phippen et al demonstrated 12 AFP-fused protein cage nanoparticles that increased the TH value to more than 50-fold that of monomeric AFP [214]. A few groups have attempted to synthesize AFP or AFGP derivatives to elucidate the underlying mechanism of action and to develop practical applications [215,216,217,218,219,220,221]. Another interesting approach is the development of cell-internalizable or -penetrating AFPs.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Antifreeze glycoproteins (AFGPs), a class of AFPs, are characterized by canonical Ala-Ala-Thr or Pro-Ala-Thr repeats with a ÎČ-D-galactosyl-(1→3)-α-N-acetyl-D-galactosamine disaccharide attached to each threonine (Carvajal-Rondanelli et al, 2011). Arctic fish AFGPs contain between 4 to 55 repeats, and AFGPs of different length may synergize, suggesting functional differences encoded into the number of tripeptide repeats and spacer sequences between them (Garner and Harding, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…AFGPs are mucin-type glycoprotein natural products isolated from select Arctic and Antarctic fish, where they play a critical role in preventing the growth of ice crystals. Structurally, AFGPs are composed of multiple copies of the repeating tripeptide Ala-Thr-Ala/Pro, in which each Thr residue is α-O-linked to the disaccharide ÎČ-D-galactosyl-(1!3)-α-N-acetyl-D-galactosamine (Scheme 18) and range in size from 4 to 50 repeat units [84,85]. In an effort to access large quantities of homogeneous AFGPs for biological studies and applications in materials science, the authors designed a convergent ligation approach to homogeneous AFGPs bearing between 4 and 32 repeat units.…”
Section: Ligation-desulfurization In Protein Synthesismentioning
confidence: 99%